Partnership Management Between Vocational Schools with the World of Business and Industry to Improve the Quality of Graduates Who Are Ready to Work - Siti Ubaidah; Sutaryat Trisnamansyah; Husen Saeful Insan; Naungan Harahap (International Journal of Nusantara Islam, 2021)
The management of the partnership between State Vocational High Schools (SMKN) and the World of Business and Industry (DUDI) has not been running optimally in its implementation, so that many partnership programs have not been realized properly. If there is no solution, it is feared that partnership activities will not work. This research aims to: To determine the planning, organization, implementation, assessment of problems and partnership solutions. The philosophical foundation of this research is progressivism philosophy, while the theoretical basis used is management theory, partnership theory and graduate quality theory. The research approach used is a qualitative approach. Data collection was carried out through: documentation study, observation and interviews, triangulation. The results showed that: (a) The planning was made together with the school committee, the principal of the vocational school, the wakasek in the field of public relations / industry, the head of light vehicle engineering, and the teacher sat with the DUDI in this case PT Teja Berlian Mitsubshi and PT Suzuki Putra Damai Bahagia, so that cooperation program agreement with DUDI; (b) Organizing by forming a team in charge of relations with DUDI and having its own main duties and functions. (c) Implementation requires cooperation with PT Teja Berlian Mitshubisi and PT Suzuki Putra Damai Bahagia, in order to improve the quality of graduates, as expected by DUDI. The implementation of the partnership program consists of: internship, production unit, competency test, teacher internship, (d) assessment of learning outcomes, internship, competency package testing and competency certification. and skills aspects (e). The problems in the partnership are: human resources managing the partnership, budget, infrastructure, the number of DUDI that is not comparable with SMK graduates and the demands of the industrial world; (f) Partnership solutions with innovation and changes in human resource management, budgets and infrastructure, the government's efforts to develop a teaching factory curriculum through partnerships, and schools to prepare students to have superior competencies, be creative, innovative, understand the digital world (IPTEK). Conclusion; There is a common goal of the partnership between SMK and DUDI, namely; improving quality according to market needs, synchronizing curriculum and synergizing school programs, increasing the absorption and placement of school graduates into the world of work. Collaboration between SMK and DUDI has an impact on improving the quality of SMK graduates, both in terms of input, process, output and outcome. Recommendations: (1) For SMK it can be used as a basis for cooperating partnerships with DUDI; (2) For DUDI it can be used as a basis for collaborating with SMKs; (3) For students it is used as a basis for increasing their competence; (4) For Researchers , can be used as a basis for further research on the Management of SMK partnerships with DUDI, to improve the quality of graduates who are ready to work in Indramayu Regency.